2009
DOI: 10.1044/ffd19.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Global Landscape of Cluttering

Abstract: The global emphasis of the International Cluttering Association (ICA) is manifested in multiple dimensions. This article focuses on two of them, namely, resources available through the ICA Web site and the results of an International Cluttering Survey (ICS), which had been presented to 25 members of the Committee of the International Representatives of the ICA. The answers of the representatives to questions regarding awareness of cluttering, definitions, professional preparation, goals for education about clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
2
2
0
2
Order By: Relevance
“…The present study revealed the high prevalence of university students who self‐identified as clutterers currently or in the past (> 20%), as well as the small number of students who have been treated by SLPs for this fluency disorder (3.5%). These findings echo previous reports on low (and even minimal) public awareness of cluttering and clinical services that may assist PwC (Reichel et al., 2010). The need for more research and education to provide information and raise awareness is crucial, as well as recognizing the problem and understanding that professional help is available.…”
Section: Discussionsupporting
confidence: 90%
“…The present study revealed the high prevalence of university students who self‐identified as clutterers currently or in the past (> 20%), as well as the small number of students who have been treated by SLPs for this fluency disorder (3.5%). These findings echo previous reports on low (and even minimal) public awareness of cluttering and clinical services that may assist PwC (Reichel et al., 2010). The need for more research and education to provide information and raise awareness is crucial, as well as recognizing the problem and understanding that professional help is available.…”
Section: Discussionsupporting
confidence: 90%
“…St. Louis -Myers 1995;Reichel 2010;Christiana 2013) és kiadványok (pl. Weiss 1964Vassné 2011;Van Zaalen -Reichel 2015) adhatnak támpontokat a szakembereknek.…”
Section: A Hadarás Terápiájaunclassified
“…Noha Reichel (2010) a folyamatos hangadás technikáját (azaz azt, hogy egy néma szünetet követő beszédegység alatt a kliens ne vegyen új levegőt, hanem addig beszéljen, amíg az adott levegőmennyiség tart) is megfelelőnek találja, több szakember a megnyilatkozások megtervezésekor a néma szünetek szabályozását preferálja inkább (LaSalle 2010; Christiana 2013), mellyel a megakadásjelenségek gyakorisága is csökkenthető lehet. A pragmatikai kompetencia fejlesztése a nonverbális kommunikáció elemzésével, a tématartás és fordulóváltás gyakorlásával (Reichel 2010), az informális és formális beszéd összehasonlításával (LaSalle 2010) érhető el. A forduló a társalgás alapegysége, a párbeszédek szervező eleme.…”
Section: A Hadarás Terápiájaunclassified
“…We believe that the growing awareness about the limits of traditional fossil fuels and their effects on climate change does play an important role. Also, focusing on more measurable factors, we mention the increasing share of electricity as mentioned above; the diffusion of distributed generation; the widespread efforts to limit local pollution; the reduction of the electricity generation cost from renewable sources (e.g., the cost of wind power and PV dropped in the last decade by 70% and 89%, respectively 19 ); and modular and fast installation of RES-based power generation plants (e.g., the commissioning time for utility-scale PV is about 6 months, while that of nuclear plants can take up to 20 years in some cases 20,21 ).…”
Section: Renewable Energy and The Early Vision Of Giacomo Ciamicianmentioning
confidence: 99%